Animal-derived lipocalin allergens exhibit immunoglobulin E cross-reactivity - Saarelainen, S.; Rytkönen-Nissinen, M.; Rouvinen, J.; Taivainen, A.; Auriola, S.; Kauppinen, A.; Kinnunen, T.; Virtanen, T. (Clinical and experimental allergy, 2008)
Summary Background Although knowledge of the IgE cross‐reactivity between allergens is important for understanding the mechanisms of allergy, the regulation of the allergic immune response and the development of efficient modes of allergen immunotherapy, the cross‐reactivity of animal allergens is poorly known. Objective The aim of this study was to characterize IgE cross‐reactivities between lipocalin proteins, including five animal‐derived lipocalin allergens and one human endogenous lipocalin, tear lipocalin (TL). Methods The recombinant proteins were validated by chromatography and mass spectrometry. The IgE‐binding capacity of the allergens was confirmed by IgE. immunoblotting and IgE immunoblot inhibition. IgE ELISA was performed with sera from 42 atopic patients and 21 control subjects. The IgE cross‐reactivities between the lipocalin proteins were determined by ELISA inhibition. Results ELISA inhibition revealed IgE cross‐reactivities between Can f 1 and human TL, between Can f 1 and Can f 2, and between Equ c 1 and Mus m 1. Low levels of IgE to human TL were found in the sera of seven dog‐allergic patients of whom six were IgE‐positive for Can f 1. Conclusion Several lipocalins exhibited IgE cross‐reactivity, probably due to the sequential identity of the proteins and also due to similarities in their three‐dimensional structures. The clinical significance of the findings needs to be elucidated. Low‐level IgE cross‐reactivity can play a role in regulating immune response to lipocalin allergens.